2021
DOI: 10.1007/s40744-021-00328-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experiences, Satisfaction, and Expectations with Current Systemic Lupus Erythematosus Treatment: Results of the SLE-UPDATE Survey

Abstract: Objectives: To provide information on systemic lupus erythematosus (SLE) patients' experiences, satisfaction, and expectations with treatments and examine the association between treatment satisfaction and patient-reported outcomes (PRO). Methods: A cross-sectional, non-interventional, online survey of US adult patients with SLE was conducted in 2019. The survey consisted of 104 questions about SLE and the following PRO instruments:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The scientific community does not know accurately the perception of our patients regarding the knowledge of the disease, just as the relationship between patients and the disease. Adherence to therapy, the impact on quality of life and work productivity, the relationship with and knowledge of the disease, and the interaction with healthcare providers and treatments are identified as major challenges in this area [ 9 17 ]. For this reason, it was decided to carry out a survey in 2020 conducted by the Spanish Lupus Federation (FELUPUS), about the perceptions and experiences of patients with SLE, in order to give voice to the patient and understand their future needs.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community does not know accurately the perception of our patients regarding the knowledge of the disease, just as the relationship between patients and the disease. Adherence to therapy, the impact on quality of life and work productivity, the relationship with and knowledge of the disease, and the interaction with healthcare providers and treatments are identified as major challenges in this area [ 9 17 ]. For this reason, it was decided to carry out a survey in 2020 conducted by the Spanish Lupus Federation (FELUPUS), about the perceptions and experiences of patients with SLE, in order to give voice to the patient and understand their future needs.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the level of S100B was significantly increased in the cerebrospinal fluid of patients with multiple sclerosis in the acute phase, while the level of S100B protein was found to be lower in the stable phase of the disease, suggesting that this protein is not limited to nerve tissue [ 30 , 31 ]. Since then, its distribution has been found in specific cell types of nonneural tissue [ 32 ]. Some scholars have found that the levels of S100B mRNA in cerebral cortex and adipose tissue are very similar [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental model of traumatic brain injury, the expression of S100B protein and mRNA increased in the injured tissue. In the same model, inhibition of the protein can reduce behavioral and pathological changes [ 32 ]. Moreover, intracerebroventricular injection of S100B has also been reported to induce dentate neurogenesis and improve cognitive function in the model of experimental traumatic brain injury (lateral fluid shock) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Pain and fatigue are independent factors associated with unemployment and disability, 5 and patients with SLE often report these symptoms to be the most challenging to self-manage and the most important treatment goals. 6 However, pain and fatigue remain largely unaddressed despite treatment advances. 7 8 Multiple factors have been found to cause, exacerbate or mitigate pain and fatigue in patients with SLE.…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…Not only do these symptoms occur in patients with active lupus, they are also reported by patients who have, otherwise, the disease under control 4. Pain and fatigue are independent factors associated with unemployment and disability,5 and patients with SLE often report these symptoms to be the most challenging to self-manage and the most important treatment goals 6. However, pain and fatigue remain largely unaddressed despite treatment advances 7 8…”
Section: Introductionmentioning
confidence: 99%